PROJECT-BASED LEARNING: MORAL ETHICS EDUCATION FOR THE COMMUNITY TO SUPPORT NATIONAL RESILIENCE IN EAST JAKARTA - Jaya Harjani, Haryanti; Sunarti, Herlina; Pujiastuti, Endang Tri; Heningtyas, Oryza Sativa; Erwin (Esteem Journal of English Education Study Programme, 2025)
The Community Service (PKM) program, themed "Moral Ethics Education for the Community to Support National Resilience in East Jakarta," will be conducted from March 2024 to December 2024. This program is an integral component of the project-based learning curriculum of Universitas Darma Persada, East Jakarta. The objective is to improve the community's comprehension of moral ethics and the significance of national resilience within the framework of effective governance. The deployed strategies consist of distributing banners, leaflets, providing direct education to the community, and disseminating educational content via YouTube. The program's effectiveness is underpinned by cooperation among the academic community of Universitas Darma Persada, government agencies in East Jakarta, the populace in ten sub-districts, and business entities. A poll of 527 students revealed a necessity for community service programs aimed at bolstering national resilience and governance, namely in the areas of improving the national legal system and anti-corruption initiatives.